2017
DOI: 10.18632/oncotarget.22966
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy and safety for bevacizumab in treating malignant pleural effusions caused by lung cancer through intrapleural injection

Abstract: Some clinical investigations have assessed the efficacy and safety of bevacizumab combined with platinum anti-cancer drugs versus platinum drugs alone in treating malignant pleural effusion (MPE) caused by lung cancer through intrapleural injection. This report is a meta-analysis of independent research conclusions. Eleven controlled trials with 769 MPE patients were included in this report. Pooled odds ratios and standardized mean difference with 95% confidence intervals were estimated using the fixed or rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…This association might be due to an improved response to the nab-PTX plus bevacizumab regimen in patients with pleural metastasis. Bevacizumab injection into the pleural cavity has been used for the management of pleural effusion and showed good benefits [52]. The combination of sb-PTX with bevacizumab has also been shown to be better than docetaxel for the management of pleural effusion from NSCLC [53].…”
Section: Discussionmentioning
confidence: 99%
“…This association might be due to an improved response to the nab-PTX plus bevacizumab regimen in patients with pleural metastasis. Bevacizumab injection into the pleural cavity has been used for the management of pleural effusion and showed good benefits [52]. The combination of sb-PTX with bevacizumab has also been shown to be better than docetaxel for the management of pleural effusion from NSCLC [53].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, intrapleural immunotherapy ushers new indications (19). Monoclonal antibodies such as bevacizumab and similar actors, cope with the metastasizing tumor causing MPE offers a logical bifocal action (39). To make a complicated picture more confusing, there is an accumulating number of observations in reference to beneficial alterations regarding therapy resistance in both directions of immunotherapies and chemotherapies as seen in pulmonary malignancies.…”
Section: Chemotherapeutics and Other Anticancer Agentsmentioning
confidence: 99%
“…Intrapleural use of bevacizumab has also been studied and seems to improve MPE control. A recent meta‐analysis has assessed efficacy and safety of intrapleural bevacizumab combined with platinum‐based systemic chemotherapy . The analysis included 11 controlled trials with 769 patients.…”
Section: Implications Of New Therapies In Nsclcmentioning
confidence: 99%
“…A recent meta-analysis has assessed efficacy and safety of intrapleural bevacizumab combined with platinum-based systemic chemotherapy. 48 The analysis included 11 controlled trials with 769 patients. Overall results showed that there was an increase in overall response rates (P = 0.003), with a decrease in the incidence of chest pain (P < 0.001) and relieved of dyspnea (P = 0.002) as compared to patients with platinum chemotherapy alone.…”
Section: Anti-angiogenic Therapiesmentioning
confidence: 99%